Web-Based Stock Management and Sales Information System for Grocery Store Jafa Partners - Hidayat, Muhammad Taufik; Mulyani, Trianti Dwi; Syafiq, Muhammad Muflih; Vernanda, Dwi (Expert Net: Exploration Journal of Technological Education Trends, 2025)
Efficient stock and sales management is essential for the smooth operation of grocery stores. However, many grocery stores still use a manual system, which is prone to errors and delays in updating information. This research aims to design and implement a web-based stock and sales management information system for grocery stores, to assist owners and employees in managing stock of goods, recording sales transactions, and monitoring reports in real-time. The system is built using web technology, which allows for easy and quick access from various devices such as computers and mobile phones. With this system, store owners can more easily monitor stock conditions, manage sales, and minimize recording errors that often occur in manual systems. The implementation results show that this system improves the efficiency of stock and sales management, and produces accurate and timely reports. In addition, this web-based system also allows store owners to monitor data and make business decisions more effectively, even remotely. Thus, this information system has the potential to improve the operational performance of grocery stores and support better decision-making.